Assessment of tissue homogenate levels of TGM1, PPL and KRT8 in a group of patients with HNSCC tumors and matched surgical margin samples - Nałęcz, Dariusz; Świętek, Agata; Hudy, Dorota; Złotopolska, Zofia; Opyrchał, Jakub; Lenckowski, Radosław; Dawidek, Michał; Aebisher, David; Strzelczyk, Joanna Katarzyna (Frontiers in Oncology, 2026)
IntroductionHead and neck squamous cell carcinoma (HNSCC) is a group of malignancies with significantly increasing incidence and mortality. Associated TGM1, PPL, and KRT proteins are involved in epithelial cell structure, adhesion, and differentiation.Objective, patients and methodsThis study aimed to evaluate TGM1, PPL, and KRT8 levels in tumors and matched surgical margin samples from 52 HNSCC patients and assess correlations with clinical and demographic variables using ELISA.ResultsNo significant differences in TGM1, PPL, and KRT8 levels were found between tumor and margin samples. However, in tumor tissue, TGM1 and KRT8 levels showed a statistically significant association with T status. In margins, PPL and KRT8 levels were also associated with T status. Additionally, PPL and TGM1 levels were correlated with N status in both tumor and margin samples, respectively. A significantly higher level of PPL was observed in OSCC tumors compared to HPSCC+LSCC. TGM1 levels in tumor and margin samples were correlated in patients with concomitant diseases. Analysis of HPV and p16 status revealed differences in PPL and KRT8 levels between tumor and margin samples. Furthermore, differences in PPL, TGM1, and KRT8 levels were observed in relation to smoking and alcohol use, distinguishing regular or occasional users from abstinent patients.ConclusionsOur results suggest that impaired TGM1, PPL, and KRT8 signaling pathways might play a role in HNSCC, indicating their potential relevance for future diagnostic and therapeutic investigations. Further studies are needed to confirm our findings, clarify the mechanistic role of these proteins in disease progression, and assess their clinical utility.